Preparation of Calcium Citrate from Chicken Eggshells and Product Characterization - Thi Thanh Binh, Nguyen; Thi Thuong, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 3, 2025)
Chicken eggshells, containing approximately 38% calcium, are a valuable source of this mineral and offer significant potential as a raw material in the pharmaceutical industry. In this study, calcium citrate was synthesized from chicken eggshells, whose main component is calcium carbonate. Calcium citrate is known for its higher solubility and bioavailability compared to the original calcium source. The synthesis was performed using a dissolution–precipitation method involving two acids through an intermediate acetate salt, resulting in a product with a purity of 98.70% and a yield of approximately 58.8%. To improve the efficiency of the synthesis, several factors were evaluated for process optimization. The optimal conditions were identified as follows: the initial reaction with an aqueous solution of acetic acid was conducted at room temperature for 5 hours, followed by a reaction with citric acid at 50 °C for 1 hour. The molar ratio of calcium acetate to citric acid was 3:2. The resulting product was a neutral salt in dihydrate form. Product characterization confirmed the identity and quality of the synthesized calcium citrate. The synthesis method is simple, environmentally friendly, and allows for solvent reuse. These results contribute to the valorization of agricultural and food industry by-products through the development of pharmaceutical ingredients. Keywords:   Chicken eggshells, containing approximately 38% calcium, are a valuable source of this mineral and offer significant potential as a raw material in the pharmaceutical industry. In this study, calcium citrate was synthesized from chicken eggshells, whose main component is calcium carbonate. Calcium citrate is known for its higher solubility and bioavailability compared to the original calcium source. The synthesis was performed using a dissolution–precipitation method involving two acids through an intermediate acetate salt, resulting in a product with a purity of 98.70% and a yield of approximately 58.8%. To improve the efficiency of the synthesis, several factors were evaluated for process optimization. The optimal conditions were identified as follows: the initial reaction with an aqueous solution of acetic acid was conducted at room temperature for 5 hours, followed by a reaction with citric acid at 50 °C for 1 hour. The molar ratio of calcium acetate to citric acid was 3:2. The resulting product was a neutral salt in dihydrate form. Product characterization confirmed the identity and quality of the synthesized calcium citrate. The synthesis method is simple, environmentally friendly, and allows for solvent reuse. These results contribute to the valorization of agricultural and food industry by-products through the development of pharmaceutical ingredients. Keywords: Calcium citrate, chicken eggshells, synthesis, optimization, characterization.